2004
DOI: 10.1111/j.1439-0426.2004.00588.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomly amplified polymorphic DNA analysis of four different populations of the Indian major carp, Labeo rohita (Hamilton)

Abstract: The level of genetic variation provides the raw material for selective improvement of a stock. Random amplified polymorphic DNA (RAPD) assay was used to assess the genetic variation in three rivers: the Halda, the Jamuna and the Padma as well as in one hatchery population of the commercially important Indian major carp, Labeo rohita. RAPD markers were amplified from DNA samples of 35 fish from each of the four populations using six decamer random primers. The polymorphic loci proportions were 0.33, 0.28, 0.28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
35
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 15 publications
8
35
3
Order By: Relevance
“…The second clade was further separated into two subgroups, Ado-Ekiti and Esaodo populations in one sub-group, and Akure, Ilesa and Owena populations in the other subgroup. The genetic distance and identity of C. gariepinus from six populations ( (Sultana et al, 2010), C. catla (Rahman et al, 2009) and L. rohita (Islam and Alam, 2004) using RAPD marker analysis. High quality bands with good reproducibility generated Garg et al (2010) who reported 172 to 1677bp in C. batrachus.…”
Section: Resultsmentioning
confidence: 99%
“…The second clade was further separated into two subgroups, Ado-Ekiti and Esaodo populations in one sub-group, and Akure, Ilesa and Owena populations in the other subgroup. The genetic distance and identity of C. gariepinus from six populations ( (Sultana et al, 2010), C. catla (Rahman et al, 2009) and L. rohita (Islam and Alam, 2004) using RAPD marker analysis. High quality bands with good reproducibility generated Garg et al (2010) who reported 172 to 1677bp in C. batrachus.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 30-40 mg of tissue (pleopod/uropod) from each collected sample was cut into small pieces with scissors, homogenised by a micro-tissue-grinder in a 1.5-ml microfuge tube and the total DNA was extracted by Proteinase-K digestion, phenol:chloroform:isoamyl alcohol extraction and the ethanol precipitation method, as described by Islam and Alam (2004). The DNA quality was checked by electrophoresis in 1% agarose gel and quantified using a spectrophotometer (Spectronic 1 Genesis TM , Spectronic Instruments Inc., USA).…”
Section: Extraction Of Dna From Shrimp Tissuementioning
confidence: 99%
“…Barman et al (2003) reported 45% of polymorphic loci in four Indian major carp population using RAPD primers. Islam and Alam (2004) observed 46.5% of polymorphic loci in four different Labeo rohita population. In the present study, relatively high level of genetic polymorphism was observed due to the small sampling size.…”
Section: Polymerase Chain Reactionmentioning
confidence: 89%